Comparison of three methods for determining saturated soil hydraulic conductivity (Damascus University Journal of agriculture sciences, 2021)
In this study three different methods were used for determining saturated soil hydraulic conductivity (ks), constant head, Rosetta code and Wind Both Rosetta and Wind methods were compared with the reference method (hydraulic constant head). In addition, statistical tests using Root Mean Square Error (RMSE) and Mean Error (ME) were used to identify the best method. The results showed that the ks estimated by both Rosetta and Wind methods were biased and underestimated comparing to the ks measured by the reference method. The Wind method showed the least RMSE value of 0.38 cm.min-1. Moreover, the estimated ks values was about 5% of the measured ks values. Furthermore, the lowest ME value of -0.27 cm.min-1 was also observed when using Wind method. On the other hand, despite the high correlation (r=0.88) between the measured and the predicted ks values, when using Rosetta method, a great RMSE value of 0.67 cm. min-1 are also found. Moreover, the estimated ks values presented about 41.9% of the measured ks values. More generally, employing both Wind and Rosetta methods for determining ks, provides an uncertainties in ks values. However, Wind method appears to be the best for obtaining a reasonable estimate of ks.